2010
DOI: 10.1002/icd.680
|View full text |Cite
|
Sign up to set email alerts
|

Chinese children's moral evaluation of lies and truths—roles of context and parental individualism–collectivism tendencies

Abstract: The present study examined Chinese children’s moral evaluations of truths and lies about one’s own pro-social acts. Children ages 7, 9, and 11 were read vignettes in which a protagonist performs a good deed and is asked about it by a teacher, either in front of the class or in private. In response, the protagonist either tells a modest lie, which is highly valued by the Chinese culture, or tells an immodest truth, which violates the Chinese cultural norms about modesty. Children were asked to identify whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 40 publications
4
57
2
Order By: Relevance
“…We used these age groups because previous studies have shown that in this age range children's lie evaluation is influenced by their perception of liar motivation, consequence of lying, and other social concerns (e.g., Fu et al, 2010;Ma et al, 2011;Xu et al, 2009). The child participants were Chinese-speaking children recruited through two primary schools in the same middle-class neighborhood in Hong Kong.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used these age groups because previous studies have shown that in this age range children's lie evaluation is influenced by their perception of liar motivation, consequence of lying, and other social concerns (e.g., Fu et al, 2010;Ma et al, 2011;Xu et al, 2009). The child participants were Chinese-speaking children recruited through two primary schools in the same middle-class neighborhood in Hong Kong.…”
Section: Participantsmentioning
confidence: 99%
“…For identification, the participant was to judge whether the protagonist had lied; for evaluation, the participant was to rate the protagonist's lie statement on a 7-point scale regarding how morally ''good'' or ''bad'' it was (1 = extremely bad and 7 = extremely good). This statement evaluation procedure was used in many past studies examining lie perception in children in similar age ranges such as Fu et al (2010), Ma et al (2011), andXu et al (2009).…”
Section: Lie Identification and Evaluationmentioning
confidence: 99%
“…First, 7- to 14-year-old children, whose modesty behavior development has been of great interest to researchers (Lee et al, 1997; Fu et al, 2010). Second, undergraduates, whose views of modesty have been examined using numerous self-report measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Lao Tzu, one of the most famous Chinese philosophers, also said, “The great rivers and seas get their kingship over the hundred lesser streams through the merit of being lower than they” (Chen, 2009). In China, such sayings have become commonly accepted truths about modesty, with Chinese children as young as nine having been socialized to behave modesty in public (Lee et al, 1997; Fu et al, 2010). For Chinese people, modesty is not only an understanding of real life but also a moral demand for ideal personality characteristics (Miao and Liang, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation